Modenar: Multi-objective differential evolution algorithm for mining numeric association rules - Alatas, Bilal; Akin, Erhan; Karci, Ali (Elsevier, 2008)
In this paper, a Pareto-based multi-objective differential evolution ( DE) algorithm is proposed as a search strategy for mining accurate and comprehensible numeric association rules ( ARs) which are optimal in the wider sense that no other rules are superior to them when all objectives are simultaneously considered. The proposed DE guided the search of ARs toward the global Pareto-optimal set while maintaining adequate population diversity to capture as many high-quality ARs as possible. ARs mining problem is formulated as a four-objective optimization problem. Support, confidence value and the comprehensibility of the rule are maximization objectives while the amplitude of the intervals which conforms the itemset and rule is minimization objective. It has been designed to simultaneously search for intervals of numeric attributes and the discovery of ARs which these intervals conform in only single run of DE. Contrary to the methods used as usual, ARs are directly mined without generating frequent itemsets. The proposed DE performs a database-independent approach which does not rely upon the minimum support and the minimum confidence thresholds which are hard to determine for each database. The efficiency of the proposed DE is validated upon synthetic and real databases. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: data mining; machine learning; evolutionary computation; multi-objective optimization; differential evolution